2005
DOI: 10.1007/s10109-005-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Multicollinearity and correlation among local regression coefficients in geographically weighted regression

Abstract: Geographically weighted regression, Multicollinearity, Local regression diagnostics, Spatial eigenvectors, Experimental spatial design,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
439
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(455 citation statements)
references
References 24 publications
6
439
0
10
Order By: Relevance
“…Local estimation is therefore particularly useful for identifying the heterogeneity and providing practical implications by visualizing the local regression coefficients (Wheeler & Tiefelsdorf, 2005). Different approaches have been proposed to estimate the parameters of local models such as GWR (Páez et al, 2002;Yang & Fik, 2014) and SALE (Pace & LeSage, 2004).…”
Section: Local Estimationmentioning
confidence: 99%
“…Local estimation is therefore particularly useful for identifying the heterogeneity and providing practical implications by visualizing the local regression coefficients (Wheeler & Tiefelsdorf, 2005). Different approaches have been proposed to estimate the parameters of local models such as GWR (Páez et al, 2002;Yang & Fik, 2014) and SALE (Pace & LeSage, 2004).…”
Section: Local Estimationmentioning
confidence: 99%
“…Previous studies have shown that a GWR model outperformed an OLS model in terms of predicting the relationship between UHI and its associated driving forces, including LUC. Mathematically, a general form of GWR model takes the following form [43]:…”
Section: The Application Of Gwr To Model the Uhi Effectmentioning
confidence: 99%
“…As early as 2005, Wheeler investigated multicollinearity problems in GWR models and pioneered the ridge regression method to introduce multiple variables and eliminate the collinearity problem in GWR models (Wheeler and Tiefelsdorf, 2005;Wheeler, 2007). Additionally, Wheeler (2009) developed the use of LASSO (least absolute shrinkage and selection operator) algorithms in GWR models to limit the effects of explanatory variable correlation.…”
Section: Introductionmentioning
confidence: 99%